The Role of Glucagon-Like Peptide-1 Receptor Agonists (GLP-1 RA) in Diabetes-Related Neurodegenerative Diseases - Cheng D; Yang S; Zhao X; Wang G (Dove Medical Press, 2022)
Dihe Cheng, Shuo Yang, Xue Zhao, Guixia Wang Department of Endocrinology and Metabolism, The First Hospital of Jilin University, Changchun, 130021, People's Republic of ChinaCorrespondence: Guixia Wang; Xue Zhao, Department of Endocrinology and Metabolism, The First Hospital of Jilin University, Changchun, 130021, People's Republic of China, Tel +86 15843081103 ; +86 18744014213, Email gwang168@jlu.edu.cn; xuezhao@jlu.edu.cnAbstract: Recent clinical guidelines have emphasized the importance of screening for cognitive impairment in older adults with diabetes, however, there is still a lack of understanding about the drug therapy. Glucagon-like peptide 1 receptor agonists (GLP-1 RAs) are widely used in the treatment of type 2 diabetes and potential applications may include the treatment of obesity as well as the adjunctive treatment of type 1 diabetes mellitus in combination with insulin. Growing evidence suggests that GLP-1 RA has the potential to treat neurodegenerative diseases, particularly in diabetes-related Alzheimer's disease (AD) and Parkinson's disease (PD). Here, we review the molecular mechanisms of the neuroprotective effects of GLP-1 RA in diabetes-related degenerative diseases, including AD and PD, and their potential effects.Keywords: glucagon-like peptide-1, diabetes mellitus, Alzheimer's disease, Parkinson's disease, cognition